2010
DOI: 10.1093/eurheartj/ehq440
|View full text |Cite
|
Sign up to set email alerts
|

Risk of congenital heart defects associated with assisted reproductive technologies: a population-based evaluation

Abstract: Cases with CHD were more likely to have been conceived following ART when compared with malformed controls. This higher risk for CHD varied specifically according to the method of ART and the type of CHD and may be due to ART per se and/or the underlying infertility of couples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 38 publications
3
76
1
5
Order By: Relevance
“…Numerous studies have indicated that children conceived through ART are at a significantly elevated risk of birth defects (Rimm et al, 2004;Bower and Hansen, 2005;Hansen et al, 2005;Olivennes, 2005;Schieve et al, 2005;Bertelsmann et al, 2008;El-Chaar et al, 2009;Goel et al, 2009;Tararbit et al, 2011;Davies et al, 2012;Mozafari Kermani et al, 2012;Wen et al, 2012). Meta-analyses have shown a 30%-40% increase in the major malformation rates for infants conceived through ART compared with NC children (Rimm et al, 2004;Hansen et al, 2005;Wen et al, 2012).…”
Section: Birth Defectsmentioning
confidence: 99%
“…Numerous studies have indicated that children conceived through ART are at a significantly elevated risk of birth defects (Rimm et al, 2004;Bower and Hansen, 2005;Hansen et al, 2005;Olivennes, 2005;Schieve et al, 2005;Bertelsmann et al, 2008;El-Chaar et al, 2009;Goel et al, 2009;Tararbit et al, 2011;Davies et al, 2012;Mozafari Kermani et al, 2012;Wen et al, 2012). Meta-analyses have shown a 30%-40% increase in the major malformation rates for infants conceived through ART compared with NC children (Rimm et al, 2004;Hansen et al, 2005;Wen et al, 2012).…”
Section: Birth Defectsmentioning
confidence: 99%
“…ART was specifically associated with significant increases in the odds of malformations of the outflow tracts and ventriculoarterial connections (adjusted OR 1.7, 95% CI 1.2âȂŞ2.4) and of cardiac neural crest defects and double outlet right ventricle (adjusted OR 1.7, 95% CI 1.1âȂŞ2.7) (Tararbit et al, 2011). A retrospective cohort study again found a higher rate of cardiovascular malformations in infants conceived by ART than controls (Wen et al, 2010).…”
Section: Congenital Malformationsmentioning
confidence: 90%
“…A recent study from Paris found cases of congenital heart disease were more likely to have been conceived using ART (Tararbit et al, 2011). ART was specifically associated with significant increases in the odds of malformations of the outflow tracts and ventriculoarterial connections (adjusted OR 1.7, 95% CI 1.2âȂŞ2.4) and of cardiac neural crest defects and double outlet right ventricle (adjusted OR 1.7, 95% CI 1.1âȂŞ2.7) (Tararbit et al, 2011).…”
Section: Congenital Malformationsmentioning
confidence: 99%
“…3 The higher risk varied with the method of assisted reproductive technique and the type of cardiac abnormality. The authors speculate that this may be due to the reproductive technology or to the underlying reason for infertility of the couple.…”
Section: Epidemiologymentioning
confidence: 99%